2022
DOI: 10.3390/nu14050918
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Intake and Insulin Resistance in 5665 Randomly Selected, Non-Diabetic U.S. Adults

Abstract: The main goal of this investigation was to evaluate the relationships between several macronutrients and insulin resistance in 5665 non-diabetic U.S. adults. A secondary objective was to determine the extent to which the associations were influenced by multiple potential confounding variables. A cross-sectional design and 8 years of data from the 2011–2018 National Health and Nutrition Examination Survey (NHANES) were used to answer the research questions. Ten macronutrients were evaluated: total carbohydrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
1
10
0
4
Order By: Relevance
“…However, HOMA-IR is susceptible to the accuracy of insulin measurements and is poorly reproducible (37). As previously mentioned, METS-IR is insulin independent and diagnostically superior to other non-insulin indexes of insulin resistance (17,38). In this study, we demonstrated that the dataset containing METS-IR had better fit efficacy for LSM and that the simpler, more accurate and more practical nature of METS-IR makes machine learning models built with METS-IR as predictor variables better applicable.…”
Section: Discussionsupporting
confidence: 59%
“…However, HOMA-IR is susceptible to the accuracy of insulin measurements and is poorly reproducible (37). As previously mentioned, METS-IR is insulin independent and diagnostically superior to other non-insulin indexes of insulin resistance (17,38). In this study, we demonstrated that the dataset containing METS-IR had better fit efficacy for LSM and that the simpler, more accurate and more practical nature of METS-IR makes machine learning models built with METS-IR as predictor variables better applicable.…”
Section: Discussionsupporting
confidence: 59%
“…Following previous studies, we used additional variables as covariates in our study ( 6 , 15 , 16 ). The demographic information included age, race (Mexican, White, Black, Other races), ratio of family income to poverty (PIR), education level (less than high school, high school, greater than high school).…”
Section: Methodsmentioning
confidence: 99%
“…METS-IR is a recently developed index that aims to be a practical and valid alternative biomarker for insulin resistance (IR) ( 14 ). Studies have demonstrated the diagnostic efficacy of METS-IR over other non-insulin-based insulin resistance indices ( 15 ). However, no studies correlating METS-IR with serum ferritin have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, T2D patients need to increase their daily intake of micronutrients [ 34 ]. In this context, several studies have demonstrated the strong antioxidant properties of vitamins that might help in improving the immune response and inflammatory processes [ 35 ]. A particular example would be riboflavin (Vitamin B2).…”
Section: Discussionmentioning
confidence: 99%